Techno-economic and environmental evaluation of the production of biodiesel from rice-straw in China - Hu, Yixuan; Chen, Jiajun; Tian, Hong; Hu, Zhangmao (Frontiers in Energy Research, 2023)
Rice straw (RS) is the residue obtained during the rice processing process, and is recognized as one of the most abundant biomass resources in the world. Approximately 800 million to 1 billion tons of rice straw are produced globally every year, and most of them are considered general waste and typically end up in landfills or incineration. This approach wastes resources and can also lead to environmental pollution. In the current study, the RS was used as the source of biodiesel production and a comprehensive process model of the RS valorization process was developed to evaluate the energy flow, production efficiency, production costs, and greenhouse gas emissions in Hunan Province, China. The evaluation results showed that the energy efficiency of biodiesel production from rice straw and the overall energy efficiency of the rice straw valorization process are reported as 52.1% and 56.1%, respectively. The minimum selling price of biodiesel, which is CNY 3.03/kg, is considerably lower than the current market prices for similar products in China. The largest proportion of the production cost of biodiesel is the cost of natural gas, followed by utilities, capital, transportation, plant maintenance and overheads, consumables, labor, and waste disposal. For the current RS valorization plant with a 5000kg/h RS feed rate, the investment payback times are 8.9 yr. and 7.1 yr. when the biodiesel is sold at the lowest (CNY 4/kg) and highest (CNY 4.6/kg) market price, respectively. Environmental analysis shows that the greenhouse gas emissions intensity of biodiesel production is 75.8 g CO2eq/MJ, which is only about 52% of traditional fossil diesel and indicating that biodiesel is an environmentally friendly energy source.